Pengaruh Tunneling Incentive, Mekanisme Bonus, Ukuran Perusahaan dan Profitabilitas terhadap Transfer Pricing - Fadilla, Nur; Budiantara, Martinus (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study is to determine whether tunneling incentive, bonus mechanism, company size and profitability have an influence on transfer pricing. This research uses secondary data using non-probability sampling method. In this study, the sample amounted to 216 manufacturing companies listed on the Indonesia Stock Exchange during 2018-2021. The data analysis method used in this research is logistic regression analysis using SPSS 25. The results of this study indicate that tunneling incentive and company size have a significant influence on transfer pricing. However, bonus mechanism and profitability have no influence on transfer pricing.